ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN NO. 16/PDT.G/2024/PTA.JK TENTANG ROYALTI LAGU SEBAGAI HARTA BERSAMA MENURUT PERSPEKTIF HUKUM POSITIF INDONESIA - NIM. A1011191142, DHEA RAMADHANTY PUTRI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The emergence of a dispute over joint property in the form of intellectual property rights over song royalties presents a new precedent in the resolution of joint property disputes, particularly regarding their distribution. This is because the plaintiff in her lawsuit wants to determine that 2/3 of the song royalties are joint property as her right. The judge's legal considerations regarding song royalties as joint property under Indonesian positive law are guided by Article 35 paragraph (1) of Law Number 1 of 1974 concerning Marriage, which states: